PENGARUH KINERJA GURU TERHADAP PRESTASI BELAJAR SISWA KELAS XI AKUNTANSI DI SMKN 6 DAN SMKN 7 KOTA SERANG - Yusina Fadla Ilmi; Della Maulia Putri; Salim Salim (FKIP, Universitas Banten Jaya, 2022)
The purpose of this study was to determine the effect of teacher performance on student achievement. This research uses descriptive quantitative method. The subjects in this study were teachers at SMKN 6 and SMKN 7 Serang City. The instrument used in this study was a questionnaire or questionnaire which was distributed directly to the teacher. In this study, prerequisite tests were carried out, namely the normality test, homogeneity test and linear regression test using the SPSS application. The results showed that 94.4% of student learning outcomes at SMKN 6 Kota Serang were influenced by good teacher performance. Meanwhile at SMKN 7 Kota Serang the percentage of teacher performance on student achievement was only 21.1%.